2020
DOI: 10.1007/s00464-019-07344-2
|View full text |Cite
|
Sign up to set email alerts
|

Doxapram as an additive to propofol sedation for endoscopic retrograde cholangiopancreatography: a placebo-controlled, randomized, double-blinded study

Abstract: Background Endoscopic retrograde cholangiopancreatography (ERCP) requires moderate to deep sedation, usually with propofol. Adverse effects of propofol sedation are relatively common, such as respiratory and cardiovascular depression. This study was conducted to determine if doxapram, a respiratory stimulant, could be used to reduce the incidence of respiratory depression. Methods This is a single-center, prospective randomized double-blind study performed in the endoscopy unit of Helsinki University Central H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For sedation, benzodiazepines, narcotics, propofol, doxapram, antihistamines, dopaminergic receptor antagonists, or combinations thereof have been tried previously. [9][10][11] Dexmedetomidine, which is an anxiolytic and sedative agent, can be used in sedation procedures without respiratory side-effects but may lead to prolonged hypotension and bradycardia. 12 The most preferred anesthetic agent in sedation is propofol.…”
Section: Discussionmentioning
confidence: 99%
“…For sedation, benzodiazepines, narcotics, propofol, doxapram, antihistamines, dopaminergic receptor antagonists, or combinations thereof have been tried previously. [9][10][11] Dexmedetomidine, which is an anxiolytic and sedative agent, can be used in sedation procedures without respiratory side-effects but may lead to prolonged hypotension and bradycardia. 12 The most preferred anesthetic agent in sedation is propofol.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that sedation with dexmedetomidine for ERCP would reduce the incidence of hypoxemia by at least 50% when compared with sedation with propofol. Based on a previous study by Jokelainen et al [14], 60.7% of patients had hypoxemia episodes with propofol-based sedation for ERCP.…”
Section: Discussionmentioning
confidence: 98%
“…However, doubts concerning its sedation-related side effects hinder its widespread clinical application, particularly during ERCP for elderly populations and those requiring prone positions. Indeed, previous studies reported a high incidence of hypotension (4.8%-19%) and hypoxemia or apnea (3.3%-60.7%) under propofol sedation during ERCP [6,14,17,18]. Dexmedetomidine is a highly selective α-2-adrenoceptor agonist with sedative, analgesic, and anxiolytic properties.…”
Section: Discussionmentioning
confidence: 99%
“…However, doubts concerning its sedation-related side effects hinders its widespread clinical application, particularly during ERCP for elderly populations and those requiring prone positions. Indeed, previous studies reported a high incidence of hypotension (4.8-19%) and hypoxemia or apnea (3.3-60.7%) under propofol sedation during ERCP [6, 14,17,18]. Dexmedetomidine is a highly selective α-2-adrenoceptor agonist with sedative, analgesic, and anxiolytic properties.…”
Section: Discussionmentioning
confidence: 99%